Inovasi Pemasaran Digital Berbasis Facebook dalam Mendukung Diversifikasi Produk Pangan Sehat dan Bergizi di Moramo, Konawe Selatan: Facebook-Based Digital Marketing Innovation to Support the Diversification of Healthy and Nutritious Food Products in Moramo, South Konawe - Asniar, Asniar; Anasari, Wa; Misdayanti, Misdayanti; Maulidiyah, Maulidiyah; Herdhiansyah, Dhian; Tamrin, Tamrin; Ansharullah, Ansharullah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This Kosabangsa community engagement program aims to strengthen the capacity of sago-processing groups and the PKK women's organization in Moramo District, South Konawe Regency, to implement digital marketing innovations for healthy, nutritious local food products through Facebook. The partner groups initially lacked knowledge and skills in digital marketing, resulting in low product visibility and limited market reach. The program was implemented through three main stages: (1) socialization and training on digital marketing, (2) mentoring in developing attractive and informative promotional content and applying marketing strategies via Facebook Marketplace and local community groups, and (3) evaluation activities through pre-test and post-test assessments, direct observation, interviews, and analysis of online sales performance. The results show a significant improvement in partners' capacity, as indicated by an increase in digital marketing knowledge from 50% to 85%, stronger content creation skills, and a wider online market reach. The program also successfully supported the diversification of nutritious sago-based food products, thereby providing additional economic value to community groups. Overall, this activity demonstrates that a community-needs-based training and mentoring approach, combined with simple digital tools, can generate rapid and significant impacts in strengthening local economies. These findings reinforce previous studies highlighting Facebook's effectiveness as a tool for community empowerment in the local food sector.